Evaluation of the favorability of the area "Les na Vorskle" of the State Nature Reserve "Belogorye" for burrowing predators’ habitat - Брусенцова, Н. О.; Український, П. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The location of the fox dens and badger setts in the area "Les na Vorskle" of the State Nature Reserve "Belogorye" has been studied. The influence of anthropogenic, biotic and abiotic factors on their location was analyzed. The identified regularities were described by means of linear regression models. Using the method of least squares (OLS) the total model for the entire territory was established. At the same time identified regularities turned out to be unstable and varied in space. The method of geographically weighted regression (GWR) was used to overcome the problem of spatial non-stationary, that was used to build local models for network of 100×100 m cells. The GWR model proved to be more efficient than the OLS model. It has a higher coefficient of determination and lower value of the Akaike information criterion. Discovered and described regularities have been used to construct maps of relatively favorable area for foxes and badgers living.